«ОТ ВАШЕЙ КУЛЬТУРЫ СЛОНЫ ДОХНУТ»: ВЕРБАЛИЗАЦИЯ ПЕРМСКОЙ КУЛЬТУРНОЙ РЕВОЛЮЦИИ (Philological Studies, 2019)
The article analyzes the verbal reactions of citizens in cultural policy, conducted by the authorities of Perm region. Analysis of verbal reactions is carried out on the material of the printed QMS, blogs, informal communication, spontaneous and organized street actions and artistic practices (2008–2013). Analysis shows that the Perm creative elite, the opposition government printing QMS and bloggers, residents of the city with low levels of education (poor vocabulary, orientation obscene forms of speech, illiteracy records) demonstrate negative verbal reactions. The capital's art historians and artists, printed QMS, bloggers and Pro-government creative elite, educated citizens and guests (including virtual) all offer the positive verbal reactions. The majority ignores the efforts of the authorities in the field of cultural policy: «the people are silent». Analysis of verbal reactions citizens shows that the authorities failed to clearly articulate the benefits of cultural project for most of the population. It is established that the main strategy in the verbalization of the Perm cultural revolution is the irony and self-irony, which act as a means of understanding the world, the path to the truth, the ironic tolerance. Irony and self-irony citizens show a discrepancy between the idea and the reality, as well as between reality and possibility. Imbalance intentions of the authorities and verbal reactions of the townspeople exist in binary oppositions, traditional for the Russian culture: centre-periphery, the sacred-profane, his – strange, new-old etc. Communicative opposition is part of the common opposition of the Russian culture in General.
Keywords: verbalization, cultural policy, regional identity, irony, self-irony, the art object